Fostering Islamic Education Talents: Art Weeks for Junior High School Students - Hasbiyallah Hasbiyallah; Tatang Muh Nasir (AL-ISHLAH: Jurnal Pendidikan, 2023)
Organizing the Islamic Religious Education Arts Week is an activity that has been planned and has an impact on developing students' creativity and personality. This research aims to describe the implementation and effectiveness of the Islamic Religious Education Skills and Arts Week in developing the talents and interests of students in the religious field in junior high schools throughout Tasikmalaya Regency. The research method used is descriptive with a qualitative approach. Data collection was carried out through documentation studies of students who took part in the Islamic Religious Education Arts Week and succeeded in winning the 2023 Islamic Religious Education Arts Week. The implementation of the Islamic Religious Education Skills and Arts Week has had a positive impact on developing students' talents and interests in the religious field in junior high schools throughout Tasikmalaya Regency. Talent and interests are also important factors in determining educational success, and recognizing students' talents helps in planning their future. Therefore, Islamic Religious Education Skills and Arts can be used as an effective method in developing students' talents and interests in the religious field. However, student supervisors still sometimes miscommunicate, so in the end, participants are disqualified. Thus, the recommendation of this research is that it is urgent to develop talent for Islamic education at Skills and Arts Week.